2022
DOI: 10.1161/circulationaha.121.055600
|View full text |Cite
|
Sign up to set email alerts
|

Salt-Induced Hepatic Inflammatory Memory Contributes to Cardiovascular Damage Through Epigenetic Modulation of SIRT3

Abstract: Background: High salt intake is the leading dietary risk factor for cardiovascular diseases. Although clinical evidence suggests that high salt intake is associated with nonalcoholic fatty liver disease, which is an independent risk factor for cardiovascular diseases, it remains elusive whether salt-induced hepatic damage leads to the development of cardiovascular diseases. Methods: Mice were fed with normal or high-salt diet for 8 weeks to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 53 publications
0
41
0
Order By: Relevance
“…In a previous study, high salt intake led to an increase in the sodium levels in liver tissue whereas it was accompanied by a decline in mitochondrial respiratory activity (38). Mitochondrial dysfunction enhances hepatocyte steatosis (38). Moreover, recent experimental studies have shown that high salt intake induces leptin resistance via activating the aldose reductase-fructokinase pathway, production of endogenous fructose and increased white adipose tissue mass via leptin production and adipocyte hypertrophy in the liver (14,35,39).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a previous study, high salt intake led to an increase in the sodium levels in liver tissue whereas it was accompanied by a decline in mitochondrial respiratory activity (38). Mitochondrial dysfunction enhances hepatocyte steatosis (38). Moreover, recent experimental studies have shown that high salt intake induces leptin resistance via activating the aldose reductase-fructokinase pathway, production of endogenous fructose and increased white adipose tissue mass via leptin production and adipocyte hypertrophy in the liver (14,35,39).…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, animal studies have revealed that high salt diet decreases the liver's antioxidant defenses (36) and may promote inflammation and fibrosis in liver (37). In a previous study, high salt intake led to an increase in the sodium levels in liver tissue whereas it was accompanied by a decline in mitochondrial respiratory activity (38). Mitochondrial dysfunction enhances hepatocyte steatosis (38).…”
Section: Discussionmentioning
confidence: 99%
“…Results from a recent study showed that mice fed with a high-salt diet displayed obvious hepatic steatosis and inflammation. All these pathological changes persisted after salt withdrawal, displaying a memory phenomenon [38]. In human studies, high sodium intake was reported to be associated with changes in inflammatory markers including tumor necrosis factor-α (TNF-α) and adiponectin [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Salt is necessary for the maintenance of normal physiological reactions in the body and evidence has shown that the average daily salt consumption is >10 g in most populations, which is double the recommendation by the World Health Organization (WHO) of 5 g/day, with the target for many countries being 6 g/day ( 1 , 2 ). High salt intake is believed to lead to a significant increase in the damage to numerous organs such as the heart, blood vessels, kidneys, and brain ( 1 4 ) and an association between high salt intake and heart failure has been established ( 5 7 ). High salt intake can cause a sustained increase in the left ventricular load, which results in functional and structural changes in the left ventricle ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%